Experience with the use of combination antithrombotic therapy in a patient with acute coronary syndrome and underlying severe coronavirus infection - D. A. Kurenkov; S. R. Shtin; T. T. Tuaeva; I. A. Machulina (Атеротромбоз, 2022)
The paper presents the experience of treating a patient with acute coronary syndrome without ST segment elevation and underlying severe novel coronavirus infection (COVID-19) complicated by polysegmental viral pneumonia and significant respiratory events. Emphasis has been placed on the use of antithrombotic therapy after endovascular treatment. A 56-year-old patient underwent respiratory support (non-invasive face mask lung ventilation followed by high-flow oxygenation), urgent diagnostic coronary angiography followed by percutaneous coronary intervention (balloon angioplasty and stenting of the right coronary artery and anterior interventricular artery). In addition to the etiopathogenetic therapy for coronavirus infection, the patient received combination antithrombotic therapy, including acetylsalicylic acid, prasugrel, FRaMon monoclonal antibodies (single exposure, intraoperatively), sodium enoxaparin. The therapy resulted in normalization of hemodynamic parameters, stable normothermia, absence of catarrhal events, improvement of exercise tolerance. A chest ultrasound imaging showed consolidation events, inflammatory markers significantly decreased, circulatory deficiency events were compensated, anginal pains did not recur. On the 20th day of hospitalization, the patient was discharged home with outpatient follow-up. The use of potent antiplatelet agents such as prasugrel or ticagrelor combined with IIb/IIIa receptor inhibitors and prolonged anticoagulant therapy can potentially improve the outcome of the disease in acute coronary syndrome with underlying severe coronavirus infection. In the presented clinical example, the use of aggressive approaches to the antithrombotic therapy did not lead to the development of significant hemorrhagic or other complications.